A computational softwre tool for satellite laser altimetry data processing. Analysis and visualisation - Silva, Bruno Miguel Pereira da (2021)
NASA’s Ice, Cloud, and Land Elevation Satellite (ICESat), the first global laser altimetry satellite, was operated between 2003 and 2009 with the primary mission objective of measuring Earth’s ice sheet mass balance, namely sea-ice thickness and ice sheet elevations. In addition of polar regions coverage, around the globe data about cloud propriety information, vegetation canopy structure and topographic data were also recorded. It has proven to be a very successful mission, operating beyond its initial 5-year goal and saw its data applied effectively in many scientific models outside its initial application scope. The ICESat-2 satellite, the follow-up of the ICESat mission, with a more capable light detection and ranging (LIDAR) instrument, was launched in 2018 and represented an advancement over the laser technology of the first ICESat mission, firing laser pulses at 10 kHz rate, instead of the previous 40 Hz. This fast-firing laser technology allows the ICESat-2’s LIDAR, called Advanced Topographic Laser Altimeter System (ATLAS), to take measurements approximately at every 0.7 meters along the satellite’s track on Earth’s surface instead the 170 meters of the previous ICESat mission. Also, each transmitted laser pulse is split in six individual beams, arranged in three pairs (each pair having a strong and a weak beam) and separated by 3 km apart, providing a multi-beam profiling of the surface. The main objective of this thesis was the development of a software tool, called ICEComb, that allows scientists and researchers to visualise and process, in a suitable way, the available altimetry data from the ICESat mission and the ICESat-2 satellite, a follow-up of the previous mission, which was launched on the 15th of September 2018 and is currently operational. ICEComb is a web-based software tool that offers its users the ability to access the available data from both missions, visualise them interactively on a geographic map, store the data products locally, explore data in a detailed, efficient and meaningful ...